Binaphthyl-Based Chiral Macrocyclic Hosts for the Selective Recognition of Iodide Anions - Zong-Cheng Wang; Ying-Zi Tan; Lin-Li Tang; Fei Zeng (Molecules, 2023)
In this study, we explorethe synthesis of binaphthyl-based chiral macrocyclic hosts for the first time. They exhibited the selective recognition abilities of iodide anions which can be favored over those of other anions (AcO−, NO3−, ClO4−, HSO4−, Br−, PF6−, H2PO4−, BF4−, and CO3F3S−), as confirmed by UV-vis, HRMS, and 1H NMR spectroscopy experiments, as well as DFT calculations. Neutral aryl C–H···anion interactions play an important role in the formation complexes. The recognition process can be observed by the naked eye.